Skizofrenia Paranoid pada Laki-laki Usia 31 Tahun: Laporan Kasus - Diva Shaffa Aisyah; High Boy Karmulrubog Hutasoit (Medula, 2026)
Paranoid schizophrenia is a subtype of schizophrenia based on PPDGJ-III classification, characterized by prominent delusions and/or hallucinations, with relatively unobtrusive affective and catatonic symptoms. This condition is often accompanied by medication non-adherence due to poor insight, which contributes to symptom exacerbation and increased risk of rehospitalization. We report a case of a 31-year-old male who presented with agitation, property destruction, and physical assault toward his mother for two days prior to admission. Symptoms first appeared five years earlier, coinciding with the death of his father, presumed to have acted as a significant psychosocial stressor. Mental status examination revealed prominent persecutory delusions alongside grade 1 insight. The patient had a history of medication refusal due to unawareness of his illness and perceived lack of need for treatment. Diagnosis of paranoid schizophrenia (F20.0) was established based on PPDGJ-III criteria. Treatment with risperidone 2x3 mg, trihexyphenidyl 2x2 mg, and valproic acid 2x250 mg alongside psychoeducation for the patient and family resulted in significant clinical improvement during hospitalization. Medication non-adherence due to poor insight was the primary factor worsening the disease course, highlighting the importance of family psychoeducation and medication supervision in long-term management.